IADC/SPE Asia Pacific Drilling Technology Conference and Exhibition 2008
DOI: 10.2118/114069-ms
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Engineered Fiber Technology - A Novel Solution to Cure Lost Circulation During Drilling: Pakistan Case History

Abstract: Losses while drilling are a serious concern to oilfield industry. Loss of expensive drilling fluid increases the overall cost of the well. Rig time spent curing the losses can represent significant cost overruns for the well. In extreme cases well control may become an issue. The general practice to control losses starts from diagnosis of the cause. The common solutions to manage the loss circulation problem include drilling fluid treatments involving decreasing the density, controlling the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Suyan et al [24] stated that the cementitious compositions admixed with synthetic fibrous LCM can be utilized to avoid a loss of return when drilling a high permeable or fracture zone. Priening et al [25] reported that the advanced engineering fibers composed of inert material are easy to disperse in the drilling fluid and can make a 3D network across the loss zone, thereby allowing the solids in the drilling fluid to form bridging plug and cure the losses. According to Droger et al [26], the performance of fiber LCM is affected by fiber concentration, fluid viscosity, fiber geometry, fracture width, and flow rate.…”
Section: Lost Circulation Materialsmentioning
confidence: 99%
“…Suyan et al [24] stated that the cementitious compositions admixed with synthetic fibrous LCM can be utilized to avoid a loss of return when drilling a high permeable or fracture zone. Priening et al [25] reported that the advanced engineering fibers composed of inert material are easy to disperse in the drilling fluid and can make a 3D network across the loss zone, thereby allowing the solids in the drilling fluid to form bridging plug and cure the losses. According to Droger et al [26], the performance of fiber LCM is affected by fiber concentration, fluid viscosity, fiber geometry, fracture width, and flow rate.…”
Section: Lost Circulation Materialsmentioning
confidence: 99%
“…• Engineered fibers to combat lost circulation during the cementation 6 o These fibers are added to the cement slurry to form a high-performance bridging network across the thief zone. o They were engineered to an optimal size of less than 0.5 in [12 mm] long and 20 microns in diameter.…”
Section: C) Gas Migrationmentioning
confidence: 99%